Isolation and molecular characterization of Brazilian turkey reovirus from immunosuppressed young poults - Rosa, Ana Carolina G. [UNESP]; Ferreira, Helena Lage; Gomes, Deriane Elias [UNESP]; Táparo, Cilene Vidovix [UNESP]; Cardoso, Tereza Cristina [UNESP] (Springer Nature, 2013)
In this study, we investigated turkey reovirus (TReoV) in tissue samples from young birds, aged 15 days. RT-PCR for TReoV detected 3.3 % positive samples and TReoV was successfully isolated in Vero cells. Histological analysis of positive bursa of Fabricius (BF) revealed atrophied follicles and lymphocyte depletion. The number of CD8+, CD4+ and IgM+ cells was lower in infected BF. Phylogenetic analysis based on S3 gene showed that the Brazilian TReoV isolates clustered in a single group with 98-100 % similarity to TReoV strains circulating in the United States. This is the first indication that TReoV infection may be a contributing factor to immunosuppression in young birds.
Keywords: Virology; Medical microbiology; Infectious diseases